Identification of Escherichia coli in Well Water in Gelogor Utara Hamlet, Kediri District, West Lombok Regency - Fatmalia, Enida; Wahyudin, Wahyudin (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Water is a very important need for human life. Wells are one of the primary means of obtaining clean water. Along with the rapid growth of settlements, water quality has decreased due to pollution. The presence of E. coli bacteria in well water indicates human and animal fecal contamination. The purpose of this study was to determine the content of E. coli in well water in Gelogor Utara Hamlet, Kediri District, West Lombok Regency. This type of research is quantitative and descriptive, involving laboratory testing. The test method used to determine the number of E. coli in the sample is the Most Probable Number (MPN) Method listed in SNI 01-2332.1-2006. The results of E. coli testing in the well were all positive samples with E. coli content >24.000 CFU/100mL and in sample 2, namely 2.400 CFU/100mL, based on Permenkes Nomor 2 Tahun 2023, namely 0 CFU/100mL, so that the drilled well water in Gelogor Utara Hamlet does not meet the requirements of the Environmental Health Quality Standards for water for Hygiene and Sanitation purposes. Based on these results, the researcher provides advice to society on maintaining the septic tank to prevent seepage in the well, disinfecting it by adding chlorine, and boiling the water before consumption. The expected impact of this research on the community is to provide information to the community regarding the E. coli content in the well water they use and to raise public awareness about the importance of managing well water used for daily needs.